Просмотр узкозазорной ливневой искровой камеры через прозрачный электрод - Ананьин П. С. Петр Семенович; Крышкин В. И.; Стерлигов А. Г.; Усов Ю. П. Юрий Петрович (1975, 1975)
Заглавие с титульного листа